THE RELATIONSHIP BETWEEN LEADERSHIP STYLES AND ORGANIZATIONAL PERFORMANCE WITH THE MODERATING EFFECT OF ENVIRONMENTAL FACTORS IN FAMILY OWNED SMALL MANUFACTURING ENTERPRISES - Pushpanathan, A. (Annamalai University, India, 2009)
Leadership in a family business is a far different challenge than leadership in any other kind of business. The leadership in the family business is aimed at helping business-owning families understand and implement the extra dimensions of leadership that family firm require. This study explores the relationship between leadership style and organizational performance in small scale manufacturing industries in Sri Lanka. This study utilized data from 220 small scale manufacturing industries those who are registered under the Chambers of Commerce in Sri Lanka. The relationship between three leadership styles – task-oriented, relationship-oriented, and participative – and firm performance were discussed with the moderating effect of environmental factors (Industry technology, family and non-family controlled firm and firm development stage). The hypotheses were tested through matched data set. The results indicated that leadership styles were directly linked to firm performance.
Keywords: Leadership Styles; Industry technology; Family and non- familycontrolled firm; Firm development stage; Performance